1994
DOI: 10.1007/bf00186361
|View full text |Cite
|
Sign up to set email alerts
|

Operative strategie bei persistenz und rezidiv in der chirurgie des prim�ren hyperparathyreoidismus

Abstract: Persisting hypercalcemia after surgery for primary hyperparathyroidism is a challenge for the surgeon: once non-parathyroid causes for the hypercalcemia have been excluded the only remaining possible causes are ineffective surgery and a failed surgery. Between 1986 and 1994, 414 patients with primary hyperparathyroidism were operated upon, 32 of whom presented with persisting hypercalcemia; 24 of these patients had their first operation in another hospital. The cause for persisting hypercalcemia was a single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…In other studies, the permanent hypoparathyroidism rate was about 60 and 20-40% in TPTX and SPTX, respectively [9][10][11]. Many reports therefore concluded that SPTX was more effective than TPTX for preventing postoperative hypoparathyroidism in patients with MEN1 [7,9,10,[13][14][15][16]19]. In contrast, a review by Thakker et al [5] recommended TPTX, while a report by Tonelli et al [8] suggested that both SPTX and TPTX with an intraoperative PTH assay are acceptable.…”
Section: Discussionmentioning
confidence: 98%
“…In other studies, the permanent hypoparathyroidism rate was about 60 and 20-40% in TPTX and SPTX, respectively [9][10][11]. Many reports therefore concluded that SPTX was more effective than TPTX for preventing postoperative hypoparathyroidism in patients with MEN1 [7,9,10,[13][14][15][16]19]. In contrast, a review by Thakker et al [5] recommended TPTX, while a report by Tonelli et al [8] suggested that both SPTX and TPTX with an intraoperative PTH assay are acceptable.…”
Section: Discussionmentioning
confidence: 98%
“…Leider wird nicht immer genau zwischen Persistenz und Rezidiv differenziert. Eine Transplantatreduktion am Arm ist f/jr den Patienten ein wenig belastender, in Lokalan~isthesie durchf/jhrbarer Eingriff, im Gegensatz zum Rezidiveingriff am Hals, der in Vollnarkose vorgenommen werden mug und ein nicht zu untersch~itzendes Risiko einer Recurrensparese in sich birgt [8]. F/Jr den Chirurgen gestalten sich beide Eingriffe problematisch: Das periphere Autotransplantat w~ichst infiltrierend in den Muskel und erschwert so seine Abgrenzung.…”
Section: Diskussiounclassified